THE KINETICS OF CaO ASSISTED PATTUKKU CHARCOAL STEAM GASIFICATION - Takdir Syarif; H Sulistyo; Wahyudi B Sediawan; B Budhijanto (Dept. of Chemical Engineering, Diponegoro University, 2018)
Abstract Coal is a solid fuel that can be converted into syngas through gasification process. To obtain optimum gasification process design and operation, in-depth understanding of the influential parameters is required. This study aims to investigate the effect of temperature on the gasification process and to obtain its kinetics parameters. The study was carried out in a tubular reactor equipped with a heater and a condenser. Steam was used as gasifying agent, while CaO was employed as a CO2 adsorbent. The charcoal from coal was subjected to gasification at temperatures of 600°C, 700°C, and 800°C. The ratio of charcoal and CaO was 1:1. The gasification process lasted for 60 minutes with gas sample was taken every 15 minutes for composition analysis. The results showed that a temperature increase of 100°C caused a proportional increase of conversion of about 75% higher. The value of activation energy (Ea) and exponential factor (ko) were 46.645kJ/mole and 328.3894/min, respectively. For mass transfer parameters, values of activation energy for surface diffusion (Es) and surface diffusivity factor (as) were 81.126 kJ/mole and 0.138/min, respectively. Keywords: gasification; mathematical model; Pattukku coal char; steam; Thin Reaction Zone Model